Nano-hydroxyapatite reinforced zeolite ZSM composites: A comprehensive study on the structural and in vitro biological properties. Issue 6 (1st May 2016) - Iqbal, Nida; Kadir, M.R. Abdul; Iqbal, Saman; Razak, Saiful Izwan Abd; Rafique, M. Shahid; Bakhsheshi-Rad, H.R.; Idris, Mohd. Hasbullah; Khattak, M.A.; Raghavendran, H.R.B.; Abbas, AA
Abstract: The bioactive composite of hydroxyapatite and zeolite-ZSM5 was successfully synthesized via the cost effective microwave wet precipitation method. The structural and morphological features were studied by X-ray diffraction, FT-IR spectroscopy and TEM/EDX analysis. These tests revealed the presence of zeolite and hydroxyapatite in the zeolite–HA composites. Spherical particles, 76–88±20 nm in size, were visible on the TEM. The simulated body fluid SBF results in vitro verified the ability of the composites to support and accelerate the growth of the HA. Furthermore, the MTT assay showed the viability of normal human osteoblasts (NHOst) on the composite, up to seven days of culture. The cell adhesion and proliferation of the normal human osteoblast (NHOst) cells onto the disc surface was much higher than the control. Overall, the ZSM–HA samples composite nanostructure can be a considered potential candidate for biomedical application.